Penyebaran Film di Platform Idlix tanpa Izin Berdasarkan Undang-Undang Hak Cipta Nomor 28 Tahun 2014 - Octavia, Inka Dwi; Zakiah, M. Uzair Jadiid; Darmayanti, Novia Dwi (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2024)
Abstract: Technological advances have made it easy to distribute unauthorized films. The distribution of unauthorized films is a copyright violation that can harm filmmakers and the creative industry. This study aims to analyze the legality of distributing films on the Idlix streaming platform based on Copyright Law No. 28 of 2014. This study uses a normative legal method with a statutory approach. Data comes from Copyright Law No. 28 of 2014, regulations related to copyright, documents and literature on copyright and film streaming platforms. The data were analyzed qualitatively using descriptive and interpretive methods. The results of the study indicate that the distribution of unauthorized films on the Idlix platform is a copyright violation that is detrimental to filmmakers and the creative industry. In addition, legal platforms are harmed by unfair competition with Idlix, and law enforcement is weak against copyright infringement on illegal streaming platforms. The distribution of films on the Idlix platform without permission from the copyright holder is a violation of Copyright Law No. 28 of 2014 and can be subject to legal sanctions. Keywords: Movies, copyright, Idlix, law. Abstrak: Kemajuan teknologi menyebabkan mudahnya penyebaran film tanpa izin. Penyebaran film tanpa izin merupakan pelanggaran hak cipta yang dapat merugikan para pencipta film dan industri kreatif. Penelitian ini bertujuan untuk menganalisis legalitas penyebaran film di platform streaming Idlix berdasarkan Undang-Undang Hak Cipta No. 28 Tahun 2014. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan. Data berasal dari Undang-Undang Hak Cipta No. 28 Tahun 2014, peraturan terkait hak cipta, dokumen dan literatur tentang hak cipta dan platform streaming film. Data tersebut dianalisis secara kualitatif dengan menggunakan metode deskriptif dan interpretatif. Hasil penelitian menunjukkan bahwa penyebaran film tanpa izin di platform Idlix merupakan pelanggaran hak cipta yang merugikan para pencipta film dan industri kreatif. Selain itu, platform legal dirugikan oleh persaingan tidak sehat dengan Idlix, dan lemahnya penegakan hukum terhadap pelanggaran hak cipta di platform streaming ilegal. Penyebaran film di platform Idlix tanpa izin dari pemegang hak cipta merupakan pelanggaran Undang-Undang Hak Cipta No. 28 Tahun 2014 dan dapat dikenakan sanksi hukum. Kata kunci: Film, hak cipta, Idlix, undang-undang.